Situs inversus in association with duodenal atresia - Ademola Olusegun Talabi; Oludayo Adedapo Sowande; Adebayo Gbenga Tanimola; Olusanya Adejuyigbe (Wolters Kluwer Medknow Publications, 2013)
Situs inversus in association with duodenal atresia is very rare. A high index of suspicion coupled with appropriate evaluation is necessary for diagnosis and operative planning. We report a case of a 5-day-old who presented with duodenal atresia associated with polysplenia and situs inversus with a review of the medical literature.